Techno-environmental mission evaluation of combined cycle gas turbines for large container ship propulsion - Alzayedi, Abdulaziz M. T.; Batra, Amit; Sampath, Suresh; Pilidis, Pericles (MDPI, 2022)
The stringent regulations set by the International Maritime Organization on pollutant emissions combined with the rise in fuel prices have stimulated research on cleaner fuels and new propulsion systems. This study describes a new method for evaluating alternative technologies and cleaner fuels that can be utilised in the marine sector to replace heavy fuel oil and diesel engines, and thus improve their performance while lowering carbon dioxide and nitrogen oxide emissions. The proposed techno-environmental technique allows consistent evaluation of simple intercooler/reheat gas and steam combined cycles fuelled by marine diesel fuel and liquefied natural gas, instead of a two-stroke diesel engine fuelled by marine diesel fuel, as a propulsion system of a large container ship. The implementation of the enhanced combined gas and steam cycles, and combined gas and steam cycles, fuelled by liquefied natural gas, increases the engine’s efficiency by 11% as compared with that of two-stroke diesel engines that run on marine diesel oil, while decreasing carbon dioxide and nitrogen oxide emissions by 44.7% and 76.3%, respectively. In addition, the advantages of using a gas and steam combined cycle to burn LNG over the gas and steam combined cycle for burning marine diesel oil are demonstrated.
Keywords: techno-environmental evaluation; gas turbine and steam turbine combined cycle; large container ship; propulsion system; liquefied natural gas; marine diesel oil; nitrogen oxide; carbon dioxide